Educational collaboration before and during the pandemic: A social network analysis of Chilean schools - Queupil, Juan Pablo (2022)
Collaborative relationships in Education have been impacted by the advancement of the COVID-19 pandemic in various latitudes of the world, making it important to explore its impact in Latin American contexts This study analyzes the impact of the pandemic on collaboration patterns of three schools in Chile. The analysis has an exploratory descriptive approach, following a Social Network Analysis (SNA) methodology, which allows the quantification of changes in collaborative relationships between the 77 schools members being analyzed. The results show that collaboration patterns changed during the pandemic, highlighting a wider distribution among educational actors’ positions and roles, and showing that the socio-sanitary emergency had an impact on their collaborative relationships.